Employee Engagement: Strategies for Reducing Turnover Intention at Mosque Marbot - Prima Jaya, Fanlia; Wahab, Abdul; Aspiannor, Akhmad; Firdaus Wardhana, Zainal (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to obtain clarity about the Perceived Organizational profile Support and Work Life Balance profiles, turnover intention profiles, marbot Mosque employee engagement profiles, as well as obtaining clarity on the relationship between Perceived Organizational Support and Work Life Balance to turnover intentions through marbot masjid employee engagement. The research method used is the Explanatory Survey Method, the object of this research is all marbot Mosques in East Banjarmasin District, then a sample is drawn and gets as many as 63 respondents who are represented by each mosque in North Banjarmasin District. Analysis using Partial Least Square (PLS). The results showed that Perceived Organizational Support partially had a significant effect on employee engagement and turnover intention, Work life Balance partially had a significant effect on employee engagement and turnover intention, Perceived Organizational Support and Work life Balance simultaneously had a significant effect on turnover intention through employee engagement. The results of this study are important for takmir masjid and marbot masjid to understand and create a strong relationship between the two so that marbot masjid 's desire to move or stop working can be reduced.